PROSPECTIVE SCIENCE TEACHERS’ VIEWS ON CAREER PLANNING AND THEIR SELF-EFFICACY LEVELS FOR CAREER DECISION-MAKING - İnce Aka, Elvan and Taşar, Mehmet Fatih (International Online Journal of Education and Teaching, 2020)
The aim of this survey study was to determine prospective science teachers’ competency levels in making career decisions and to determine their views on career planning. The participants were 88 prospective middle school science teachers enrolled at the Science Teaching Program of a state university during the spring 2018. The data were collected through the Career Decision-Making Self-Efficacy Scale (CDSS) (Ulaş & Yıldırım, 2016) and open-ended, written extended response questions prepared by the researcher. The findings revealed that for career decision-making, the participants had high efficacy levels; they were predominantly doing their own career planning; and that they were influenced by their family members’ views. They envisioned career planning as a long-term process starting at birth and encompassing the whole school and professional lives. The majority thought that their career decisions affected every aspect of their lives.